Isolation and Biochemical Analysis of Leaf Protein Concentrates from the Leaves of Shorea robusta - Singh, Suman; Varshney, V.K.; Wahi, Nitin; Khan, Lutful Haque (Pakistan Journal of Nutrition, 2014)
Shortage of supply of good quality protein for meeting the requirements of increasing animal and human population has necessitated search for additional sources. Leaf protein concentrate (LPC), a concentrated form of proteins derived from the foliage of plants, is an inexpensive and most abundant source of available protein. Their protein value equals that of most animal products. Trees have been suggested as a potential source of LPC and the production of protein from tree leaves is advantageous over crops as they do not involve the recurring cost of cultivation. Shorea robusta is planted on large scale in India. The potential of its leaves as protein source has not been investigated. The present communication describes the isolation of LPCs, mineral elements from the leaves of Shorea robusta and its chemical evaluation. Fresh and matured leaves of Shorea robusta yield fairly good amount of LPC (5.96 g) per 100 g leaves. It was also found to contain very high amount of ash (9.24%), which consisted of calcium, Iron, Phosphorus, Potassium, Sulphur micronutriets. Comparing all the biochemical analysis, the LPCs recovered from Shorea robusta shows fairly good amount of protein-37.25%, fat-7.41%, nitrogen free extract-37.85%, total carbohydrates-45.5%, total soluble sugar-1.94% along with low amount of anti-nutritional factors such as total phenolics and total saponins. Thus it was inferred that the leaves of the Shorea robusta have potential for its use in production of LPCs. However, detailed studies regarding minerals, vitamins, in-vitro digestibility, toxicity testing and amino acid compositions are needed to be carried out to standardize the use of leaves as a source of LPCs.